Przeszkody małżeńskie w VI i VII wieku na podstawie postanowień synodów merowińskich - Oko, Jan (Śląskie Studia Historyczno-Teologiczne, 2023)
The transition of time between Ancient Times and the Middle Ages is the period when the culture of Europe emerges and when the Roman-Christian and Teutonic cultures meet. It is manifested in many areas, among others, in matters concerning marriage. This article deals with particular issues concerning marital laws, namely marriage impediments. Although the Merovingian councils do not know the term “marriage impediments” itself, they enumerate a few situations which impede contracting a marriage. Successive impediments are described in subsections of the article. They are: consanguinity and kinship, constraints, holy orders and monastic vows. The article also treats re-marriages or marriages with Jews which were also forbidden in some cases. The frequency of above mentioned impediments and study of Teutonic customs enable us, at least partially, to present problems with which the Church of the Merovingian period had to deal.